Continuity and discontinuity in the peopling of Europe one hundred fifty years of Neanderthal study - Condemi, Silvana; Weniger, Gerd-Christian.; SpringerLink (Online service). (Dordrecht Springer Netherlands Imprint: Springer, 2011)
Since the Western world first became aware of the existence of Neanderthals, this Pleistocene human has been a regular focus of interest among specialists and also among the general public. In fact, we know far more about Neanderthals than we do about any other extinct human population. Furthermore, over the past 150 years no other palaeospecies has been such a constant source of discussion and fierce debate among palaeoanthropologists and archaeologists. This book presents the status of our knowledge as well as the methods and techniques used to study this extinct population and it suggests perspectives for future research.
Neanderthals and emergent palaeoanthropology 50 years ago / F. Clark Howell -- One hundred fifty years of Neanderthal discoveries : continuity and discontinuity / Silvana Condemi -- The genus Homo : origin, speciation and dispersal / Winfried Henke and Thorolf Hardt -- Before the Neanderthals : hominid evolution in Middle Pleistocene Europe / Ian Tattersall -- The earliest European human peopling after the recent discoveries : early Neanderthals or different lineages? / Francesco Mallegni -- The Gran Dolina-TD6 human fossil remains and the origin of the Neanderthals / José María Bermúdez de Castro ... [et al.] -- The hominid fossils from China contemporaneous with the Neanderthals and some related studies / Wu Liu and Xiujie Wu -- Behavioral and cultural origins of Neanderthals : a Levantine perspective / Naama Goren-Inbar -- Discontinuities in the faunal assemblages and early human populations of central and western Europe during the middle and late Pleistocene / Wighart von Koenigswald -- Neanderthal geographical and chronological variation / Bernard Vandermeersch and María Dolores Garralda -- A preliminary approach to the Neanderthal speciation by distance hypothesis : a view from the shoulder complex / Jean-Luc Voisin -- Facts and ideas in Paleolithic growth studies (paleoauxology) / Anne-Marie Tillier -- Dental development and age at death of a Middle Paleolithic juvenile hominin from Obi-Rakhmat Grotto, Uzbekistan / Tanya M. Smith ... [et al.] -- Computerized reconstruction of prenatal growth trajectories in the dentition : implications for the taxonomic status of Neandertals / Patricia Smith ... [et al.] -- Endostructural characterisation of the Regourdou 1 Neanderthal proximal arm : bilateral asymmetry and handedness / Virginie Volpato ... [et al.] -- A three-dimensional look at the Neanderthal mandible / Katerina Harvati, Nandini Singh, and Elisabeth Nicholson López -- Integration and homology of ?Chignon? and ?Hemibun? morphology / Philipp Gunz and Katerina Harvati -- Virtual synthesis of the skull in Neanderthals by FESS / Ulrich Witzel -- Neandertal mtDNA from a late Pleistocene human mandible from the Cova del Gegant (Spain) / Juan Luis Arsuaga ... [et al.] -- Towards Neanderthal paleogenomics / David Caramelli ... [et al.] -- Twelve years of Neandertal genetic discoveries : state-of-the-art and future challenges / Ludovic Orlando and Catherine Hänni -- Radiocarbon dating the Middle to Upper Palaeolithic transition : the demise of the last Neanderthals and the first appearance of anatomically modern humans in Europe / Olaf Jöris ... [et al.] -- Archaeological, paleontological and genomic perspectives on late European Neandertals at Vindija Cave, Croatia / Ivor Janković ... [et al.] -- Late Neandertals and early modern humans in Europe, population dynamics and paleobiology / Erik Trinkaus -- Aliens from outer time? : why the ?human revolution? is wrong, and where do we go from here? / João Zilhão -- Neandertals and the roots of human recency / Milford H. Wolpoff and Rachel Caspari -- Epilogue : 150 years of Neanderthal research - a hopeless situation but not serious / Gerd-Christian Weniger.
Electronic reproduction.
Keywords: Neanderthals -- Congresses; Fossil hominids -- Congresses; Paleolithic period -- Congresses; Neanderthals -- Europe -- Congresses; Fossil hominids -- Europe -- Congresses; Paleolithic period -- Europe -- Congresses; Prehistoric peoples -- Europe -- Congresses; Human evolution -- Europe -- Congresses; Excavations (Archaeology) -- Europe -- Congresses; Electronic books